2021
DOI: 10.2147/idr.s302126
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk of COVID-19 and Related Factors Among University Students in Ethiopia During School Reopening

Abstract: Background: The novel coronavirus disease 2019 (COVID-19) has posed a great threat to the public. University students living in school compound with groups and sharing a common cafeteria are more susceptible to contract and spread the virus. Risk perception multiplies fear and anxiety that triggers precautionary action. However, research is scant in this particular field. Objective: To assess the perceived risk of COVID-19 and its associated factors among University Students in Northeast Ethiopia during school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 23 publications
5
26
3
1
Order By: Relevance
“…This perception could impact correct face mask usage and uptake of other SOPs. However, our findings don't corroborate those in studies conducted in south Western Ethiopia (53.4%), Ghana (68.3%) and Sierra Leone (75%) (Asefa et al, 2020, Serwaa et al, 2020, Tadese et al, 2021 which indicated higher risk perceptions. Our findings show the need for more efforts toward sensitization of students in rural areas on their risk and susceptibility to COVID-19.…”
Section: Discussioncontrasting
confidence: 99%
“…This perception could impact correct face mask usage and uptake of other SOPs. However, our findings don't corroborate those in studies conducted in south Western Ethiopia (53.4%), Ghana (68.3%) and Sierra Leone (75%) (Asefa et al, 2020, Serwaa et al, 2020, Tadese et al, 2021 which indicated higher risk perceptions. Our findings show the need for more efforts toward sensitization of students in rural areas on their risk and susceptibility to COVID-19.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of our study contradicted the research results of Mants’ study, which found that 96.5% of Canadian university students rated COVID-19 as moderately or very severe (Mant et al 2021 ). The disparity in risk perceptions could be attributed to differences in the study population, study period, data collection tool and procedures, and the level of virus spread across countries and communities (Tadese et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of COVID-19 preventive measures was 96.4%, 95.4%, 94.1% and 84.3% in Japan, Pakistan, Saudi Arabia and Jordan, respectively 8–11. In Africa, COVID-19 preventive behaviour was 88.8%, 92% and 56.8% in Nigeria, Egypt and Ethiopia, respectively 12–14…”
Section: Introductionmentioning
confidence: 99%